Needs Analysis of the Development of TPACK (Technological Pedagogical Content Knowledge) Integrated Green Chemistry e-Module Prototype - Yulis, Putriade Rahma; Fauziah, Nurul (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The current condition is still limited in integrated chemistry teaching materials with TPACK(TechnologicalPedagogicalContentKnowledge)especially in Green Chemistry material because this material is a new material in the realm of the merdeka curriculum in 10th Grade of E Phase in Senior High School. Teachers only use printed books as teaching materials or additional materials made in the form of PPTs and modules from the Ministry of Education.This is one of the causes of several problems in learning. This research is the initial stage as the basis for the development of an integrated green chemistry e-module with TPACK. The development model used is ADDIE which consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation.This research is limited to the needs analysis stage which includes the analysis of Learning Outcomes (CP) of E Phase, and analysis of topics on chemistry materials, analysis of problems and needs of teachers and problems and needs of students. The data collection instrument uses interviews and questionnaires. The subjects of this study consisted of 12 chemistry teachers and 84 students from Riau and Kepulauan Riau Province. The results of this preliminary analysis research include an analysis of the subject matter of 10th Grade class while there are 5 material topics and based on the questionnaire the needs of these topics include the topics with the highest percentage to be developed into e-modules because they are considered difficult by most respondents. Then the results were also obtained that there are still some shortcomings in the teaching materials used today, so that 94% of students and 100% of teachers stated that they need the development of TPACK-based teaching materials.